My robot Sophia [videorecording (DVD)] - Hanson, David; Siskind, Sarah Rose; Hanson, Elaine (Gravitas Ventures, 2025)
Inventor David Hanson is on a relentless quest to bring compassion to Sophia, the most recognized humanoid robot in the world. My Robot Sophia poses pressing questions around AI and what it means to be human.